Exploiting CRISPR-Cas to manipulate Enterococcus faecalis populations - Karthik Hullahalli (eLife, 2017)
CRISPR-Cas provides a barrier to horizontal gene transfer in prokaryotes. It was previously observed that functional CRISPR-Cas systems are absent from multidrug-resistant (MDR) Enterococcus faecalis, which only possess an orphan CRISPR locus, termed CRISPR2, lacking cas genes. Here, we investigate how the interplay between CRISPR-Cas genome defense and antibiotic selection for mobile genetic elements shapes in vitro E. faecalis populations. We demonstrate that CRISPR2 can be reactivated for genome defense in MDR strains. Interestingly, we observe that E. faecalis transiently maintains CRISPR targets despite active CRISPR-Cas systems. Subsequently, if selection for the CRISPR target is present, toxic CRISPR spacers are lost over time, while in the absence of selection, CRISPR targets are lost over time. We find that forced maintenance of CRISPR targets induces a fitness cost that can be exploited to alter heterogeneous E. faecalis populations.